PREPARATION, CHARACTERIZATION AND ANALYTICAL STUDIES OF 4-((2,6-DIHYDROXYPHENYL) DIAZENYL)-5-HYDROXYNAPHTHALENE-2,7-DISULFONIC ACID AS A NEW AN ANTI-BREAST CANCER (MCF-7) - Mosa, Saleel; Ali, Hanan (International Journal Multidisciplinary (IJMI), 2025)
Objective: The novel azo dye 4-((2,6-dihydroxyphenyl)diazenyl)-5 hydroxynaphthalene-2,7-disulfonic acid (S3) was synthesized and characterized. Method: The FTIR analysis confirmed strong -SO₃H and -OH peaks, that affecting solubility and electronic properties. The UV-Vis studies demonstrated solvent-dependent absorption shifts, with DMSO exhibiting the highest λmax due to extended conjugation and strong π-π* transitions, influencing λmax shifts, with a bathochromic shift in basic conditions and hypsochromic shift in acidic media. Spectrophotometric titration confirmed a clear neutralization process, where S3 acted as a pH-sensitive. Result: In vitro toxicity assessments demonstrated that S3 exhibited non-hemolytic effects on red blood cells, while MTT assays on MCF7 cancer cells confirmed dose-dependent cytotoxicity. The IC₅₀ value (315.2 µg/mL) highlighted its potential as an anticancer agent, with a high correlation coefficient (R² = 0.9582). Novelty: These findings suggest that S3 could serve as a dual-functionality compound, acting as both a pH indicator and an anticancer agent.